Formulation Standardization of panelitas de leche: preliminary study - Ortiz-Álvarez, José Rafael; Cortés-Jiménez, Amanda; Ramírez-Navas, Juan Sebastián (Revista de Ciencias Agrícolas, 2017)
"Panelitas de leche" (PDL) are a candy-like belonging to the family of Dulce de Leche. The objective of this study was to produce a PDL formulation with whey added. Eight experiments were performed, all mono-factorials. The effects of different raw materials and the processing conditions on the sensory characteristics of the PDL were studied. A sensory profile of commercial PDL was previously obtained to use as a reference when evaluating the food products obtained after each experiment. The best formulations of PDL - similar to commercial PDL- were obtained using corn flour, substituting 4% of sugar for panela, whey diluted by 50% in weight, and milk replacement for whey at ratios of 1:0.25, 1:0.538 or 1:1. The processing conditions included a temperature of 90°C with an estimated cooking time of 150 minutes, and a final concentration of 79°Bx.